2016
DOI: 10.1016/j.jcf.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the species of Achromobacter in a French Cystic Fibrosis Centre and multilocus sequence typing analysis reveal the predominance of A. xylosoxidans and clonal relationships between some clinical and environmental isolates

Abstract: This study is a first approach in understanding the global epidemiology of Achromobacter species in CF. These results confirm the high prevalence of the species A. xylosoxidans among CF patients, reveal the worldwide distribution of some STs and point out the potential role of environmental sources of contamination. More studies are needed to search for relationships between species and/or ST and pathogenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 28 publications
7
30
0
1
Order By: Relevance
“…A similar diversity was observed in the USA (14 different Achromobacter species and genogroups from 341 CF patients) [15], in Spain (six different species and genogroups from 14 CF patients) [16], in the UK (12 species and genogroups from 96 CF patients) [17] and in France (11 species and genogroups from 47 CF patients) [18]. In congruence with these studies, A. xylosoxidans was the Achromobacter sp.…”
supporting
confidence: 79%
“…A similar diversity was observed in the USA (14 different Achromobacter species and genogroups from 341 CF patients) [15], in Spain (six different species and genogroups from 14 CF patients) [16], in the UK (12 species and genogroups from 96 CF patients) [17] and in France (11 species and genogroups from 47 CF patients) [18]. In congruence with these studies, A. xylosoxidans was the Achromobacter sp.…”
supporting
confidence: 79%
“…Biofilm production in A. xylosoxidans was previously found to be significantly associated with CF patient infections (9). It may also facilitate horizontal gene transfer between bacteria, promoting the spread of antimicrobial resistance (9,34), which may provide a differential adaptive stability in the environment and airways to establish chronic infection (5,24,35). We found that A. xylosoxidans demonstrated increased biofilm biomass production compared to that of other species (A. insuavis and A. dolens).…”
Section: Discussionmentioning
confidence: 57%
“…Studies have attributed persistent Achromobacter infections predominantly to A. xylosoxidans (2,11,12,18), with a few exceptions, including A. insuavis and A. dolens (5,6). We now know that this may represent a broader species distribution.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Of note, the species A. mucicolens and A. animicus were until then isolated from human samples only. Most species identified from the domestic environment in our study were considered minor CF-associated species in several studies (8,(26)(27)(28). For example, A. mucicolens, a species described in 2013 on the basis of five human clinical isolates, including one from CF sputum (29), and currently only scarcely reported for CF, was the major species identified in domestic environments in this study.…”
mentioning
confidence: 49%